Umbilical Cord Teratoma Presenting as Ruptured Omphalocele - Fabian Doktor; Jan-Hendrik Gosemann; Peter Zimmermann; Manuela Siekmeyer; Holger Stepan; Martin Lacher (European Journal of Pediatric Surgery Reports, 2022)
Congenital mature teratomas of the umbilical cord are extremely rare. We report on a girl who presented with a ruptured omphalocele and a 7 cm mass connected to the umbilicus, which we resected on the first day of life. Histology revealed mature umbilical cord teratoma . On the 29th day of life, a secondary laparotomy was necessary to address the associated intestinal malformations (megaduodenum, stenotic small bowel with duplication and malrotation). After a prolonged hospital stay, we discharged the patient in age-appropriate conditions. Antenatal diagnosis of an umbilical cord tumor can be challenging in the presence of an omphalocele. Given the high prevalence of associated malformations, the finding of umbilical cord teratoma should be followed by a detailed and comprehensive neonatal workup for additional abnormalities.